Relationship Between Smoker Male Partner and Intrauterine Insemination Success in Kasih Ibu General Hospital Denpasar - Albert Salim; Yukhi Kurniawan; I Gusti Ngurah Pramesemara (Universitas Airlangga, 2021)
Background: Assisted reproductive technology, one of which is intrauterine insemination (IUI) allows infertile couples to get pregnant. The pregnancy success of IUI procedure varies among individuals. Objective: The study aim is to determine whether there is a relationship between smoker male partners and IUI success. Methods: This research is an analytic study with cross-sectional approach conducted at Kasih Ibu General Hospital Denpasar with purposive sampling technique. There are 35 male couples aged 25-50 years who underwent the IUI procedure selected as samples. The research data was gathered from patient's medical records and statistically analyzed using the Chi-Square test. Results: The study found that of the 35 samples, 13 (37.1%) were smokers, whereas 22 (62.9%) male partners were non-smokers. There were 6 (17.1%) samples’ partners who were pregnant after undergoing the IUI procedure, and 29 (82.9%) samples’ partners were not pregnant. It was found that there was no significant relationship between male partner smokers and the success of IUI at Kasih Ibu General Hospital Denpasar (p=0.832). However, in descriptive analysis and relative risk calculation, smoker male partner is less likely to achieve pregnancy than non-smoker’s male partner (RR=0.85). Conclusion: Smoker male partners may not contribute to IUI success. Further studies should be done with a higher number of samples, multicenter, and more controlled risk factors to make it more accurate in determining the relationship.